A Survey of Avian Fauna in Kabale Municipality, South Western Uganda - Sarah, Nachuha; Fortunate, Twagiramaria (Advances in Research, 2021)
Collection of data on avifaunal diversity is a crucial component for monitoring the effects of habitat changes on biodiversity. A rapid cross sectional survey to document common bird species present in Kabale municipality was conducted over a period of 3 months. Birds were categorized into families and the Shannon–Weaver (H') diversity index and the abundance of all the species was calculated. A total of 1770 bird individuals consisting of 67 species, 34 families were recorded, with an overall species diversity of 3.41. The Grey Crowned Crane (Balearica regulorum) an endangered species and the Woolly–necked Stork (Ciconia episcopus) a vulnerable species were among the species recorded. The relatively high diversity is probably attributed to the presence of trees on farmland areas within the municipality. This combination seems to provide various food sources or nesting and perching grounds for the birds. Information generated by this study will serve as a benchmark for monitoring of changes in species diversity and composition over time. In addition, the list of birds will be useful to residents of the area and the many ecotourists who visit Kabale town.